2017
DOI: 10.1155/2017/8594051
|View full text |Cite
|
Sign up to set email alerts
|

Pounding Dynamic Responses of Sliding Base-Isolated Rectangular Liquid-Storage Structure considering Soil-Structure Interactions

Abstract: The soil-structure interaction (SSI) is simulated by an artificial boundary, the pounding that occurs between the sliding base-isolated rectangular liquid-storage structure (LSS) and the surrounding moat wall is considered, the instantaneous pounding is simulated using the Hertz-damp model, and a simplified mechanical model with two particles and four degrees of freedom is established. Dynamic equation is obtained using Hamilton principle; effects of SSI, initial gap, and friction coefficient on the pounding r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Mostly pounding elements with a linear or a nonlinear spring damper system, following the Hertz law, are applied (cf. [2,[25][26][27][28][29]). In this paper, a pounding element with a linear spring is chosen to describe the impact forces in both horizontal and vertical directions by interpolating the node tractions.…”
Section: Methods Of Contact Constraint Enforcementmentioning
confidence: 99%
“…Mostly pounding elements with a linear or a nonlinear spring damper system, following the Hertz law, are applied (cf. [2,[25][26][27][28][29]). In this paper, a pounding element with a linear spring is chosen to describe the impact forces in both horizontal and vertical directions by interpolating the node tractions.…”
Section: Methods Of Contact Constraint Enforcementmentioning
confidence: 99%
“…For more than four decades, a wide variety of studies have been conducted to develop various base isolation devices and to study their effects on the improvement of the seismic performance of steel tanks [8][9][10][11][12][13][14]. However, several factors influence the seismic responses of structures [15,16], and in the case of base-isolated liquid storage tanks, they may have adverse effects leading to an increase in seismic demands compared to the fixed base condition [17][18][19]. For example, Bagheri and Farajian [17] showed that the base isolation may experience an excessive displacement when the system is subjected to near-fault excitations with severe pulses, resulting in a dramatic increase in the displacement of the impulsive mass and, consequently, base shear and overturning moment.…”
Section: Introductionmentioning
confidence: 99%
“…Shrimali et al and Dumne et al have researches on seismic response behavior of coupled buildings with base isolation and MR damper between adjacent floor levels [9,10]. Base isolated rectangular liquid-storage tank is investigated by Cheng et al to identify the pounding behavior due to near-field pulse-like earthquakes [11]. Gap dampers are also proposed to reduce displacement responses of base-isolated structures [12,13].…”
Section: Introductionmentioning
confidence: 99%